Enhancing the Income of Mie Lidi Microenterprises in the Underdeveloped Village of Banjarsari, Demak Regency Through the Implementation of Solar-Powered Portable Automatic IoT Blower Technology - Sunu Arsy Pratomo; Purwanto Purwanto; Fatchur Roehman; Muhammad Ikhsan Setiawan; Che Zalina Zulkifli; Zulfiya Khabirova (Malikussaleh University, Aceh, Indonesia, 2026)
This study investigates the integration of solar energy technologies to improve operational efficiency, reduce production costs, and enhance income generation among micro and small enterprises in rural Indonesia. The research focuses on the mie lidi processing sector in Banjarsari Village, Demak Regency, where traditional drying practices remain highly dependent on weather conditions, resulting in inconsistent production quality and limited productivity. To address these challenges, the study introduces a solar-powered Portable Automatic Internet of Things (IoT) Blower designed to automate and optimize the drying process while utilizing renewable energy as the primary power source. The proposed system incorporates two 550-watt monocrystalline solar panels integrated with IoT-based monitoring and automated airflow control mechanisms. Performance evaluation demonstrates that the solar energy system generates an average of 6.69 kilowatt-hours (kWh) of electricity per day, equivalent to approximately 187.2 kWh per month. Meanwhile, the blower requires only 0.864 kWh of energy per day, representing 12.9% of total energy production, thereby creating a substantial energy surplus that supports long-term operational sustainability. The implementation of the system produces estimated monthly electricity cost savings of IDR 270,447.24, significantly reducing operational expenditures for local enterprises. Beyond economic benefits, the automated drying technology enhances production consistency by eliminating dependence on fluctuating weather conditions and reducing processing delays. The integration of renewable energy and smart automation also contributes to environmental sustainability through lower carbon emissions and reduced reliance on fossil-fuel-based electricity. The findings indicate that solar-integrated IoT drying systems offer a practical, scalable, and environmentally friendly solution for strengthening rural entrepreneurship, increasing productivity, and supporting sustainable economic development. Furthermore, the proposed model provides a replicable framework that can be adopted by other rural communities with similar climatic and socio-economic conditions to promote energy independence and resilient local industries